Meningkatkan Aktivitas, Keterampilan kerjasama, Berpikir Kritis dan Hasil Belajar Peserta Didik Menggunakan Model Pembelajaran CANGKAL dan Media WORDWALL pada Muatan IPS Kelas V SDN Basirih 1 Banjarmasin - Muhammad Dihyatul Qalbi; Akhmad Riandy Agusta; Fathul Jannah; Wahdah Refia Rafianti (Jurnal Pendidikan Sosial Dan Konseling, 2025)
The problem in this study is the low activity, cooperation skills, critical thinking, and student learning outcomes. This is due to one-way learning, lack of student activeness, and monotonous learning. The effort to overcome it using the CANGKAL model and WORDWALL media. This study aims to describe teacher activities, analyse the improvement of student activities, cooperation skills, critical thinking, and learning outcomes. This research is a PTK with the subject of fifth grade students of SDN Basirih 1 Banjarmasin, semester II of the 2023/2024 school year. The results showed significant improvement in all aspects, so it is recommended to use this model to improve the quality of learning.